Drumlin Formation Time: Evidence from Nothern and Central Sweden - Hattestrand, Clas; Gotz, Svea; Naslund, Jens-Ove; Fabel, Frederick; Stroeven, Arjen (Blackwell Publishing Ltd, 2015)
Large-scale drumlins occur abundantly throughout central and northern Sweden. Whereas many drumlins in the north are an integral part of a relict glacial landscape > 100,000 years old, those to the south are generally interpreted as of last deglaciation age. Typically, the latter ones have not been overprinted by younger glacial landforms. Despite this apparent difference in formation history, drumlins in both regions have similar directional and morphological characteristics. A systematic analysis of >3000 drumlins in (i) areas within relief landscapes, (ii) areas with an ambiguous deglaciation age assignment, and (iii) areas within deglacial landscapes, indicates that these latter deglaciation drumlins differ clearly in both shape and size from drumlins in the other two types of landscapes. In addition, numerical modelling indicates that basal melting conditions, a prerequisite for drumlin formation, prevailed only for a very limited time over much of northern Sweden during the last deglaciation, but lasted for longer periods of time during earlier stages of the Weichselian. A reconnaissance radionuclide bedrock exposure date from the crag of a large drumlin in the relict landscape indicates that glacial erosion, and presumably drumlin formation, at this location predated Marine Isotope Stage 7. We conclude, therefore, that the large-scale drumlins of central and northern Sweden did not form during the last deglaciation, or during any other specific ice flow event. Instead, we suggest that they were formed by successive phases of erosion and deposition by ice sheets of similar magnitude and configuration.